2005
DOI: 10.1007/s00441-005-1093-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mussel gill cells in vivo and in vitro

Abstract: Mussel gill cells are attractive models in ecotoxicological studies because gills are the first uptake site for many toxicants in the aquatic environment; gill cells are thus often affected by exposure to pollutants. Our aim was to characterize mussel gill cells in vivo and in vitro by using morphological, histochemical and functional end-points. In paraffin sections stained with haematoxylin-eosin, three zones were distinguished in the long central gill filaments: frontal, intermediate and abfrontal. Various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 36 publications
2
52
0
5
Order By: Relevance
“…Therefore, high levels of hypotaurine and thiotaurine seem to be a common characteristic of the gills of bathymodiolin mussels. High levels of hypotaurine in the gill are to be expected, considering its function is to detoxify sulfides, because the gill is the first organ that is in contact with ambient water (Gómez-Mendikute et al 2005). High levels of hypotaurine and thiotaurine throughout the genus is consistent with the possibility that shifts in habitat and symbiont types have occurred several times within the genus (Jones et al 2006, Lorion et al 2010.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, high levels of hypotaurine and thiotaurine seem to be a common characteristic of the gills of bathymodiolin mussels. High levels of hypotaurine in the gill are to be expected, considering its function is to detoxify sulfides, because the gill is the first organ that is in contact with ambient water (Gómez-Mendikute et al 2005). High levels of hypotaurine and thiotaurine throughout the genus is consistent with the possibility that shifts in habitat and symbiont types have occurred several times within the genus (Jones et al 2006, Lorion et al 2010.…”
Section: Discussionmentioning
confidence: 66%
“…This may be due to its high amino acid content, an important component of the mollusc diet (Renault et al 1995). Recommendations on how often media should be changed vary from every 2 days (Takeuchi et al 1994), 4 days (Kleinschuster et al 1996), 3 weeks (Brewster and Nicholson 1979), to not at all (Gomez-Mendikute et al 2005). It was found that for the zebra mussel a media change every 4-6 days was suitable.…”
Section: Media Changementioning
confidence: 99%
“…However, some success has been reported in mantle explants from bivalves with the detection of DNA synthesis after 13 days in culture (Koyama and Aizawa 2000), mitotic figures from 7-day-old cultures (Cornet 2006), and functional viability after 40 days (Barik et al 2004). Gill cells were also maintained in suspension for up to 18 days with 50% viability (Gomez-Mendikute et al 2005). Numerous published reports of cell reproduction were suspected of having been contaminated by thraustochytrid species (common marine and freshwater heterotrophic protists; Rinkevich 1999) and as far as the authors are aware despite being able to maintain living cells in culture for aquatic invertebrates, the ability to encourage cell reproduction and the growth of differentiated tissue in vitro has still not yet been achieved.…”
Section: Media Changementioning
confidence: 99%
See 1 more Smart Citation
“…Studies examined the gill tissue and analysed the cells of freshwater mussels, Pyganodon cataracta, Utterbackia imbecillis and Ligumia substrata (Unionid mussels), and reported different cellular types, including the 'cells rich in mitochondria', which play a significant role in active uptake of ions and solute transport into and out of the gills (Kays et al 1990;Schwartz and Dimock, 2001). In vivo and in vitro gill epithelium analyses were also performed in the seawater mussel Mytilus galloprovincialis (Gómez-Mendikute et al 2005). Findings reported the presence of ciliated (58 %) and nonciliated (42 %) cells, including epithelial cells and haemocytes (4.3 %).…”
Section: Introductionmentioning
confidence: 99%